Vascularized Posterior Iliac Crest Bone Grafting: Indications, Techniques, Clinical Outcomes, and Alternatives - Winocour, Sebastian J.; Schultz, Kelly P.; Davis, Matthew J.; Abu-Ghname, Amjed; Bohl, Michael; Ropper, Alexander E.; Maricevich, Marco; Reece, Edward M. (Seminars in Plastic Surgery, 2021)
Pseudarthrosis is a feared complication of spinal fusion procedures. Currently, the gold standard in prevention or treatment of pseudarthrosis is placement of nonvascularized iliac crest bone autograft. While rates of fusion are significantly higher in patients with use of nonvascularized bone autografts than with allografts, patients who have previously failed lumbar arthrodesis or those at a high risk for pseudarthrosis may benefit from a more robust, vascularized bone graft with enhanced osteogenicity. In this article, we discuss the use of iliac crest vascularized bone grafts as an adjunct for high-risk patients undergoing lumbosacral spine arthrodesis.
Keywords: vascularized bone graft; spinoplastic reconstruction; iliac crest; autograft; spinal fusion; pseudoarthrosis